Molecular docking and molecular dynamics simulation studies on Thermus thermophilus leucyl-tRNA synthetase complexed with different amino acids and pre-transfer editing substrates - Rayevsky, A.V.; Tukalo, M.A. (Вiopolymers and Cell, 2016)
Aim. To investigate the structural bases for the amino acid selectivity of the Thermus thermophilus leucyl-tRNA synthetase (LeuRSTT) aminoacylation site and to disclose the binding pattern of pre-transfer editing substrates. Methods. Eight amino acids proposed as semi-cognate substrates for aminoacylation and eight aminoacyl-adenylates (formed from AMP and eight amino acids) were prepared in zwitterions form. The protein structure with a co-crystallized substrate in the aminoacylation site [PDBID: 1OBH] was taken from RCSB. Docking settings and evaluation of substrate efficiency were followed by twofold docking function analysis for each conformation with Gold CCDC. The molecular dynamics simulation was performed using Gromacs. The procedures of relaxation and binding study were separated in two different subsequent simulations for 50ns and 5ns. Results. The evaluation of substrate efficiency for 8 amino acids by twofold docking function analysis, based on score values,has shown that the ligands of LeuRSTT can be positioned in the following order: Leu>Nva>Hcy>Nle>Met>Cys>Ile >Val. MD simulation has revealed lower electrostatic interactions of isoleucine with the active site of the enzyme compared with those for norvaline and leucine. In the case of aminoacyl-adenylates no significant differences were found based on score values for both GoldScore and Asp functions. Molecular dynamics of leucyl-, isoleucyl- and norvalyl-adenylates showed that the most stable and conformationally favorable is leucine, then follow norvaline and isoleucine. It has been also found that the TYR43 of the active site covers carboxyl group of leucine and norvaline like a shield and deflected towards isoleucine, allowing water molecules to come closer. Conclusions. In this study we revealed some structural basis for screening unfavorable substrates by shape, size and flexibility of a radical. The results obtained for different amino acids by molecular docking and MD studies well correlate with the experimental data on the first stage of aminoacylation. MD study of the aminoacyl-adenylates revealed that difficulty of some amino acids activation can be caused by two reasons: excessive flexibility due to the size or structure and quick hydrolysis of intermediate substrate with nucleophilic attack by water molecules. Мета. Вивчення структурних особливостей, що забезпечуютьселективність аміноацилюючого сайту лейцил-тРНК синтетази із Thermus thermophilus (LeuRSTT) по відношенню до амінокислот, і пояснення механізму зв’язування субстрату претрансферного редагувааня. Методи. Вісім амінокислот, запропонованих в якості субстратів аміноацилювання і вісім аміноациладенилатів (сформованих з АМФ і восьми амінокислот) були підготовлені у вигляді цвіттер-іонів. Кристалічна структура білка із субстратом в аміноацилюючому сайті [PDBID:1OBH] була отримана із RCSB бази даних. Параметри докінгу та оцінка ефективності лиганда припускали дворазовий аналізу конформацій за допомогою пакету Gold CCDC. Моделювання молекулярної динаміки проводилось з використанням Gromacs. Процедури релаксації і детального дослідження були розділені на два послідовних моделювання тривалістю 50 нс і нс. Результати. Оцінка ефективності зв’язування 8 амінокислот була визначена завдяки аналізу на основі двох оціночних функцій і показала, що ліганди LeuRSTT за цими властивостями можна розташувати в наступному порядку: Leu> Nva> Hcy> Nle> Меt> Cys> Ile > Val. МД показала нижчі електростатичні взаємодії ізолейцину з активним сайтом ферменту у порівнянні з норваліном і лейцином. У випадку аміноациладенилатів істотних відмінностей не було знайдено. Молекулярна динаміка лейцил-, ізолейцил- і норваліладенилату показала, що найбільш стабільним і конформаційно вигідним субстратом є лейцин, а не норвалін і ізолейцин. Крім того, було виявлено, що TYR43 в активному сайті екранує карбоксильні групи лейцину і норваліну і відхиляється убік в присутності ізолейцина, дозволяючи молекулі води наблизитися. Висновки. В цьому дослідженні ми виявили деякі причини відбору субстратів в залежності від форми, розміру і гнучкості радикала. Результати для різних амінокислот, отримані за допомогою молекулярного докінгу і МД, добре корелюють з експериментальними даними по першому етапу аміноацилювання. МД аміноациладенилатів показала, що складність в активації деяких амінокислот може бути викликана двома причинами: надмірною гнучкістю через розмір радикалу або структуру і швидким гідролізом проміжного субстрату під час нуклеофільної атаки молекулами води. Цель. Изучение структурных особенностей, обеспечивающих селективность аминоацилирующего сайта лейцил-тРНК синтетазы Thermus thermophilus (LeuRSTT) в отношении связывания аминокислоты, и механизма связывания субстрата пре-трансферного редактирования. Методы. Восемь аминокислоты предложенных в качестве родственных субстратов аминоацилирования и восемь аминоациладенилатов (сформированых из АМФ и восьми аминокислот) были подготовлены в виде цвиттер-ионов. Кристаллическая структура белка в комплексе с субстратом в аминоацилирующем сайте [PDBID: 1OBH] была взята из базы данных RCSB. Параметры докинга и оценка эффективности лиганда предполагали двукратный анализ каждой конформации при помощи Gold CCDC. Моделирование молекулярной динамики проводилось с использованием Gromacs. Этап релаксации и, собственно, изучение связывания были разделены на два последовательных моделирования по 50ns и 5ns. Результаты. Оценка эффективности связывания 8 аминокислот проводилась на основе значений двух оценочных функций и показала, что лиганды можно расположить по активности в следующем порядке: Leu> Nva> Hcy> Nle> Мет> Cys> Ile > Val. МД симуляции показали более низкие электростатические взаимодействия изолейцина с активным сайтом фермента по сравнению с таковыми для норвалина и лейцина. В случае аминоациладенилатов существенных различий не было обнаружено. МД лейцил-, изолейцил- и норвалиладенилата показала, что наиболее стабильной и благоприятной является конформация лейцина, а не норвалина и изолейцина. Кроме того, было обнаружено, что Tyr43 активного сайта экранирует карбоксильную группу лейцина и норвалина, но отклоняется в сторону в присутствии изолейцин, позволяя молекуле воды приблизиться. Выводы. В этом исследовании мы описали некоторые причины отсева различных по форме, размеру и гибкости радикала субстратов. Результаты для различных аминокислот, полученные в результате молекулярного докинга и МД симуляций, хорошо коррелируют с экспериментальными данными первого этапа аминоацилирования. Отдельное изучение аминоациладенилатов показало, что сложность активации некоторых аминокислот может быть вызвана двумя причинами: чрезмерной гибкостью, в связи с размером или формой радикала, и быстрым гидролизом промежуточного субстрата в момент нуклеофильной атаки молекулами воды.